The accuracy of the denver developmental screening test II in identifying developmental delay in high risk newborns at Charlotte Maxeke Johannesburg Academic Hospital - Madini, Katlego Babo Boitumelo Jostinah (My University, 2020)
Background: The Denver Developmental Screening Test II (Denver II) is used to assess the development of high risk newborns at a tertiary hospital in Johannesburg. Aim: This article aims at assessing the accuracy of the Denver II in identifying developmental delay 6 in high risk newborns. The Bayley Scales of Infant and Toddler Development III (BSID III) is used as a gold standard test, to determine the level of agreement between the two tests. Method: This is a retrospective descriptive study. The study population consisted of both normal and high 10 risk neonates born between 1 July 2013 and 31 December 2015. The results of infants that had both a Denver II and a BSID III were assessed. Results: The sensitivity of the Denver II in identifying developmental delay was .8% and 44.0% for a 14 BSID III composite score cutoff of <85 (“at risk”), and <70 (“handicapped”) respectively. The Denver II had a specificity greater than 90%.for both BSID III composite cutoff values. The agreement between the results of the two tests were represented by a Kappa value of 0.111 for the BSID III assessed as “at risk” (p = 0.014), and 0.423 for the BSID III assessed as “handicapped” (p < 0.000). Conclusion: The Denver II is not accurate in identifying developmental delay. There is a slight to moderate agreement between the Denver II and the BSID III tests. The Denver II is not a suitable screening test for use in South African infants, and further research is required.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in the Branch of Paediatrics to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020
Keywords: SDG-3: Good health and well-being